Silicon in the morphometry and germination of corn seeds for silage - Brennecke, Kathery; Sarro, Letícia; Dian, Paulo Henrique Moura; Ferrari, Maria Helena; Bertipaglia, Liandra Maria Abaker; Amancio, Weberson Donizete de Castro (Revista Agrogeoambiental, 2020)
As a forage, the objective of this study was to evaluate corn plant, seed development and seed germination in response to silicon application at different doses pathway leaf. The experimental design was randomized blocks with four treatments of different doses of silicon, equivalent to 0.0, 100.0, 200.0 and 300.0kg ha-1 of calcium silicate, at 22%, and four replications, applied pathway leaf. It was observed that the applied silicon did not influence any of the plant morphometric variables, however it altered the ear characteristics regarding weight and diameter, at which the best response was observed in the application equivalent to 100kg silicate-1 ha-1. The applied silicon doses showed no significant differences in morphological characteristics such as plant height, first ear height, stem diameter, number, and leaf angles. Significant differences were found in the weight of one thousand grains, and by increasing the silicon dose, there was an increase in the weight of one thousand grains and in the germination; in 7 days, it was found a decrease in germination percentage as well as in the percentage of normal seedlings when increasing the calcium silicate doses. It was concluded that the application of calcium silicate via leaf increased the stem diameter, the ear of corn and the weight of one thousand seeds and decreased the germination percentage in seven days and the appearance of normal seedling.